Effects of age on the identification of emotions in facial expressions: a meta-analysis - Ana R. Gonçalves; Carina Fernandes; Rita Pasion; Fernando Ferreira-Santos; Fernando Barbosa; João Marques-Teixeira (PeerJ, 2018)
Background Emotion identification is a fundamental component of social cognition. Although it is well established that a general cognitive decline occurs with advancing age, the effects of age on emotion identification is still unclear. A meta-analysis by Ruffman and colleagues (2008) explored this issue, but much research has been published since then, reporting inconsistent findings. Methods To examine age differences in the identification of facial expressions of emotion, we conducted a meta-analysis of 24 empirical studies (N = 1,033 older adults, N = 1,135 younger adults) published after 2008. Additionally, a meta-regression analysis was conducted to identify potential moderators. Results Results show that older adults less accurately identify facial expressions of anger, sadness, fear, surprise, and happiness compared to younger adults, strengthening the results obtained by Ruffman et al. (2008). However, meta-regression analyses indicate that effect sizes are moderated by sample characteristics and stimulus features. Importantly, the estimated effect size for the identification of fear and disgust increased for larger differences in the number of years of formal education between the two groups. Discussion We discuss several factors that might explain the age-related differences in emotion identification and suggest how brain changes may account for the observed pattern. Furthermore, moderator effects are interpreted and discussed.